2018
DOI: 10.1002/rrq.237
|View full text |Cite
|
Sign up to set email alerts
|

Who Gets to Read What? Tracking, Instructional Practices, and Text Complexity for Middle School Struggling Readers

Abstract: In this study, the authors used the Early Childhood Longitudinal Study, Kindergarten Class of 1998–99 to examine the instructional time allocation and instructional practices in eighth‐grade English language arts classes for struggling readers, as measured by track level. The authors also analyze the titles and text complexity of the last three books assigned to students. The authors found that track level continues to be a significant predictor of what happens instructionally in the classroom. Struggling read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…However, there is little evidence to suggest that whole language or balanced literacy approaches are more common in schools that are racially segregated and/or serve mainly low-income children. In fact, the available evidence suggests the opposite: Children in under-resourced schools and children who have been labeled “poor readers” are more likely to be taught “the basics” (e.g., letter-sound correspondence) and less likely to be given opportunities to engage with complex ideas found in texts (Bacon, Connor, & Ferri, 2016; Eppley & Dudley-Marling, 2019; Haberman, 1991; Northrop & Kelly, 2019).…”
Section: A Manufactured Crisis?mentioning
confidence: 99%
“…However, there is little evidence to suggest that whole language or balanced literacy approaches are more common in schools that are racially segregated and/or serve mainly low-income children. In fact, the available evidence suggests the opposite: Children in under-resourced schools and children who have been labeled “poor readers” are more likely to be taught “the basics” (e.g., letter-sound correspondence) and less likely to be given opportunities to engage with complex ideas found in texts (Bacon, Connor, & Ferri, 2016; Eppley & Dudley-Marling, 2019; Haberman, 1991; Northrop & Kelly, 2019).…”
Section: A Manufactured Crisis?mentioning
confidence: 99%
“…Even when overall patterns of adaptation are generally positive, as in reading instruction, maladaptation in specific contexts may arise. For example, focusing on differences by student track level in 8th grade, Northrop and Kelly (2019) found that on a variety of dimensions, including the complexity of the texts teachers select for students, instruction is more disparate than would be predicted based on student achievement level. This finding is consistent with literature on teacher adaptations in expectations and evaluative standards (Kelly & Carbonaro, 2012;Stevens & Van Houtte, 2011).…”
Section: Collective Teacher Adaptationmentioning
confidence: 99%
“…Based on this evidence, the guide’s authors recommend five instructional practices: Provide explicit vocabulary instruction, provide explicit comprehension strategy instruction, provide opportunities for extended discussion of text meaning and interpretation, increase student motivation and engagement in literacy learning, and make available intensive and individualized interventions for struggling readers that can be provided by trained specialists. This guide is widely read among policymakers and has been cited hundreds of times by researchers, including Baye and colleagues (2019) and in other recent RRQ articles (Boardman, Boelé, & Klingner, 2018; Northrop & Kelly, 2019; Proctor, Silverman, Harring, Jones, & Hartranft, 2020).…”
mentioning
confidence: 99%